(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Old English literature represents the earliest surviving body of English literary expression, dating from approximately the seventh to the eleventh century. It reflects a unique synthesis of Germanic heroic culture and Christian ideology. This article examines the historical background, major genres, dominant themes, and stylistic features of Old English literature, with particular reference to Beowulf, elegiac poetry, and religious writings. The study argues that Old English literature not only preserves the cultural identity of early medieval England but also establishes the thematic and structural foundations of later English literary tradition.